ESSAY ON HUMAN (RACE RELATIONS) IN THE UNITED STATES - Bedell, Frederick D. (International Journal of Research -GRANTHAALAYAH, 2018)
This essay speaks to the context of domination and subordination in particular as it pertains to White Supremacy/White Privilege as manifested in the history of slavery and “Jim Crow” in the United States. It is within this historical context one can discern the present status of race relations in the United States that continues to foster race discrimination through the policies of the ethnic majority (white) power structure, e.g.-institutional racism, voter suppression laws, gerrymandering of voter districts and banking policies to name a few areas. The research of books, papers, television interviews and personal experiences provides a testament to present government policies that endeavor to maintain a social construct of dominance and subordination by the white power structure in the United States.